Plectranthus ecklonii Benth: A Comprehensive Review Into its Phytochemistry and Exerted Biological Activities - Antão, Ana Ribeirinha; Bangay, Gabrielle; Domínguez-Martín, Eva María; Díaz-Lanza, Ana María; Ríjo, Patrícia (Frontiers in Pharmacology, 2021)
Ethnopharmacological Relevance: Plectranthus genus (Lamiaceae family) contains several species with acknowledged ethnopharmacological uses, such as gastrointestinal and respiratory-related problems, due to their anti-inflammatory, antibacterial and antifungal properties. The bioactivity of isolated medicinal compounds from this genus justifies the increased interest in recent times for species of Plectranthus, placing them in the spotlight for natural product drug development. Aim of the study: To the best of our knowledge, this is the first review on the biological activities of Plectranthus ecklonii Benth.. As such, the aim of this review was three-fold: 1) to summarize the chemical compounds isolated from P. ecklonii; 2) to collate the biological activities and mechanisms of action of these compounds from in vitro studies; and 3) to evaluate the documented uses and potential applications of this species, in order to postulate on the direction of pharmaceutical uses of this species. Materials and methods:An extensive database retrieval was performed using the electronic databases Web of Science, PubMed, Google Scholar and ScienceDirect. The search criteria consisted of the keywords "Plectranthus ecklonii", "Plectranthus ecklonii + review", "Plectranthus ecklonii + diterpenes" or "Plectranthus ecklonii + abietanes", "ecklonii + parviflorone D", searched individually and as combinations. Eligibility criteria were set out and titles in English, Portuguese and Spanish were reviewed, with all references included dating from 1970 to 2021. A total of 169 papers were selected and included. Chemical structures were drawn using ChemDraw 20.0, CID numbers were searched in PubChem and the PRISMA diagram was created using PowerPoint 2012. Results:To date, a total of 28 compounds have been isolated from P. ecklonii, including diterpenes, triterpenes, flavonoids, and hydroxycinnamic acids. Most focused on the antimicrobial action of its constituents, although compounds have demonstrated other bioactivities, namely antioxidant, anti-inflammatory and antitumor. The most recent studies emphasize the diterpenoids, parviflorone D (1), particularly with the help of nanotechnology. Conclusions: The widespread ethnobotanical and traditional uses of P. ecklonii can be scientifically justified by a range of biological activities, demonstrated by isolated secondary metabolites. These bioactivities showcase the potential of this species in the development of economically important active pharmaceutical ingredients, particularly in anticancer therapy.